PENERAPAN JELAJAH ALAM SEKITAR BERBASIS PAIKEM PADA MATERI PENCEMARAN LINGKUNGAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMP NEGERI 4 LANGOWAN - Rumawir, Meylinda E.; Pendong, Dientje F.; Posumah, Dany Ch (SOSCIED, 2024)
Applying appropriate teaching methods and approaches can aid students in constructing better understanding and actively engaging in learning, while also assisting teachers in addressing issues such as student inactivity and boredom. This study aims to examine the improvement of student learning outcomes through the implementation of an Nature Exploration Approach-based PAIKEM in teaching Environmental Pollution to 7th-grade students at SMP Negeri 4 Langowan. The research method utilized is Classroom Action Research (CAR) following Kemmis and Taggart's model. After implementing the JAS-based PAIKEM approach in the teaching process, the post-test results of the second cycle showed significant improvement. Out of 26 students, 25 students completed the test, achieving a 96.15% passing rate, with only one student not completing it, accounting for 3.85%, and the class average score was 87.5. These results indicate a substantial enhancement in student learning outcomes, reaching the predefined classical mastery level of 96.15%. Consequently, it can be concluded that utilizing the surrounding environment as a learning resource through the JAS-based PAIKEM approach effectively enhances the learning outcomes of 7th-grade students at SMP Negeri 4 Langowan regarding environmental pollution